Lengger Mask Dance Performance: Art Tourism-Based Art Education (Catharsis, 2022)
The Lengger Mask Dance is a traditional populist dance and a type of social dance performed by two dancers: the lengger dancer and the mask dancer as escort. The performance of the Lengger Mask Dance and tourist packages differ. The Lengger Mask Dance performance typically lasts between six and eight hours; however, the performance at Ting Njanti Market is compressed and only lasts one hour. The focus of the research is the Lengger Giyanti Mask Dance performance. The purpose of this research is to analyze the performance process. The researcher employs both an ethnochoreological and an art education approach. The research method is qualitative, and the design is a case study. Before the show, during the show, and after the show were identified as the three major phases of the performance process by the study. There are three processes in the pre-performance phase: training, workshop, and rehearsal. The performance stage is comprised of four processes: warm-up, public performance, larger events/contexts that support public performances, and cool-down. The stage following the performance is comprised of three processions: critical responses, archives, and memories. This research concludes that there are ten processes in a performance, which are divided into three main sections: before the show, during the show, and after the show.